THE MEDIATION EFFECTS OF SATISFACTION IN THE INFLUENCE OF FUNCTIONAL VALUE AND EMOTIONAL VALUE ON CUSTOMER LOYALTY ONLINE ETHNIC BATAK PRODUCTS IN PEMATANGSIANTAR - nutri ciasi; liharman saragih; elfina damanik (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of functional and emotional value on online customer loyalty of ethnic batak products in Pematangsiantar City with the intermediary variable of satisfaction as a partial and simultaneous mediating variable. The study used a quantitative descriptive approach. Data was collected using a questionnaire method via google form to 96 respondents, which were samples obtained through accidental sampling and sample determination using the Lemeshow formula. The data analysis techniques used in this research are data instrument test, classical assumption test, multiple linear regression analysis, R2 determinant coefficient test, t test, F test and path analysis using the IBM SPSS V.26 program. The results showed that the functional and emotional variables had a significant positive direct influence on loyalty, respectively 0,017 and 0,005. The indirect influence value between functional variables through satisfaction with loyalty is 0.273 and between emotional variables through satisfaction with loyalty is 0.351.